Political Orientation of Middle Class in Naya Muluk - Lamsal, Chakra Pani (Tribhuvan University Journal, 2022)
The research is focused on the political position of the middle-class in the selected area of Banke and Bardiya district. The objective of the research is to explore the middle-class formation process, its position, and the political orientation with its connection to caste/ ethnicity. It adopts the structuralist theory and the relative class power model. It has followed the mixed method of research. This study adopted the gradational concepts of class and measured them based on the self-perceived notion. Documentary resources, questionnaire surveys, and telephone interviews are used for data collection. Diversification of profession and tertiary activities, bureaucracy, expansion of education and activities of NGO/ INGO, adoption of privatization, and inclusive representation are major factors in the formation of the middle class. Middle-class people like to be more active in civil society and social organizations than in a political party. It opens the door to a new gateway of research on the middle class and helps to promote common values and a roadmap without exploitation and repression of the ruling class. Despite the postmodern claim of the death or irrelevance of class, the class concept is still relevant as an analytical factor and more as a source of political power. The new middle classes are focused on governance, service delivery, and transformation in addition to social justice, inclusion, and empowerment.